Self-enforcing constitutional amendments rules: a dialogue with Richard Albert’s Constitutional Amendments: Making, Breaking, and Changing Constitutions - Benvindo, Juliano Zaiden (Revista de Investigações Constitucionais, 2020)
Richard Albert’s groundbreaking book Constitutional Amendments: Making, Breaking, and Changing Constitutions surely provides the most extensive analysis of constitutional amendments rules ever published. Particularly relevant is that, unlike part of the constitutional literature that overly stresses normative assumptions, Albert brings important insights about how constitutional amendment rules can influence certain outcomes and provide incentives for political players’ behaviors. By drawing from rational choice theory, this Article aims to show the value of self-enforcing constitutional amendment rules for constitutional design. Although Richard Albert does not directly work with rational choice language, he certainly knows how to operate some of its premises when examining cases, raising hypotheses, creating models, and suggesting constitutional frameworks. His book is a relevant example of how constitutional design, when not excessively dominated by normative assumptions that are taken for granted, can be the much-needed response to challenges that a strong reliance on those normative assumptions may fail to overcome.